2012
DOI: 10.1158/1078-0432.ccr-12-0912
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Clinicopathologic Associations, and Molecular Spectrum of ERBB2 (HER2) Tyrosine Kinase Mutations in Lung Adenocarcinomas

Abstract: Background Activating mutations in the tyrosine kinase domain of HER2 (ERBB2) have been described in a subset of lung adenocarcinomas (ADCs) and are mutually exclusive with EGFR and KRAS mutations. The prevalence, clinicopathologic characteristics, prognostic implications, and molecular heterogeneity of HER2-mutated lung ADCs are not well established in US patients. Experimental Design Lung ADC samples (n=1478) were first screened for mutations in EGFR (exons 19 and 21) and KRAS (exon 2) and negative cases w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
364
9
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 418 publications
(406 citation statements)
references
References 44 publications
28
364
9
5
Order By: Relevance
“…85 In-frame insertions in exon 20 and substitutions at S310 are the most common mutations seen, and are typically mutually exclusive with other recurrent alterations, including mutations in EGFR, KRAS, and BRAF, as well as rearrangements involving ALK and ROS1. Insertions in exon 20 are variable, with most being a 12ebase pair duplication of codons 775e778 encoding amino acids YVMA, 81 and are more commonly observed in younger patients and patients with no smoking history. De novo ERBB2 amplification may occur with or without ERBB2 mutation, 82,84,86 with highly variable reported rates of cooccurrence from 0% to 87%.…”
Section: Lung Cancer Molecular Testing Guideline Updatementioning
confidence: 99%
See 1 more Smart Citation
“…85 In-frame insertions in exon 20 and substitutions at S310 are the most common mutations seen, and are typically mutually exclusive with other recurrent alterations, including mutations in EGFR, KRAS, and BRAF, as well as rearrangements involving ALK and ROS1. Insertions in exon 20 are variable, with most being a 12ebase pair duplication of codons 775e778 encoding amino acids YVMA, 81 and are more commonly observed in younger patients and patients with no smoking history. De novo ERBB2 amplification may occur with or without ERBB2 mutation, 82,84,86 with highly variable reported rates of cooccurrence from 0% to 87%.…”
Section: Lung Cancer Molecular Testing Guideline Updatementioning
confidence: 99%
“…De novo ERBB2 amplification may occur with or without ERBB2 mutation, 82,84,86 with highly variable reported rates of cooccurrence from 0% to 87%. 81,84,86 Although differences in methods and criteria defining amplification levels may be responsible for these observed discrepancies and require standardization, the higher prevalence of ERBB2 amplification independent of ERBB2 mutation suggests that mutation and amplification could represent distinct markers and therapeutic targets in lung cancer. 89 ERBB2 amplification has also been reported rarely as a secondary event in patients with sensitizing EGFR mutations and as a potential mechanism of resistance following treatment with EGFR inhibitors.…”
Section: Lung Cancer Molecular Testing Guideline Updatementioning
confidence: 99%
“…HER‐2 kinase domain mutations can be categorized as: missense point mutations, small in‐frame insertions or duplications which almost occurring in exon 20 and in frame deletions. Among these mutations, the in‐frame insertions or duplications in exon 20 are the most frequently encountered types of mutations 22, 30, 31, 32. In addition, we also take the HER‐2 splice variants into account, including p95HER‐2 and Δ16HER‐2.…”
Section: Introductionmentioning
confidence: 99%
“…A typical tumor contains two to eight driver mutations that can affect as many as 12 key cellular signaling pathways. Reported genetic alterations for lung adenocarcinoma include: EGFR (32,(42)(43)(44)(45)(46)(47), KRAS (42,(48)(49)(50)(51)(52), BRAF (53)(54)(55)(56), and ERBB2 (formerly HER2) (45, 56-60) driver mutations; ROS1 (32,(61)(62)(63), KIF5b-RET (32,64,65), and EML4-ALK rearrangements (20,45,57,61,(66)(67)(68)(69)(70); and other gene amplifications (20). An estimated 50% of lung adenocarcinomas in patients in Western populations have either an EGFR or KRAS driver mutation (42).…”
Section: Clinical Issuesmentioning
confidence: 99%
“…Most studies conducted to date have demonstrated a higher rate of EGFR mutations among Asian patients than Western patients, and these studies are consistent with those findings. Nonetheless, the LI and DOGAN studies, among others (42,45,57,77,85,86), establish that a significant number of smoking patients harbor EGFR mutations in their tumor specimens. These findings stand in contrast to those reported in some of the early EGFR studies (47,(71)(72)(73), which seemed to indicate that an EGFR mutation occurred exclusively in nonsmokers.…”
Section: Driver Mutationsmentioning
confidence: 99%